Advancements, frontiers and analysis of metal oxide semiconductor, dye, electrolyte and counter electrode of dye sensitized solar cell. (February 2022) - Agrawal, Anupam; Siddiqui, Shahbaz A.; Soni, Amit; Sharma, Ganesh D.
Highlights: Structure and operational principle of DSSC are provided along with their equations. Advancement of various TCO substrate and sealing materials in DSSCs were summarized. Progress in photoanode, different types of dye and electrolyte used in DSSC were elaborated. Improvement on the CE in DSSCs with special focus on Pt-TCO free CE were highlighted. Abstract: The Dye-sensitized solar cell (DSSC) is globally investigated technology due to their attractive characteristics such as low-cost, simple fabrication, flexible, transparent, variety of colour, sensitive to diffuse light and eco-friendly photovoltaic (PV) technology and have capabilities for commercial application. These characteristics are particularly well suited for integrated PV in buildings and automotive, as well as indoor or portable light applications. DSSC is a photo-electrochemical device comprises of a photo-anode consists of wide band metal oxide semiconductor (MOS) layer sensitized with dye, counter electrode (CE) coated with platinum or other material and an electrolyte which is sandwiched between the photo-anode and counter electrode. Therefore, to enhance the DSSC's performance, a comprehensive study to understand the fundamental and recent research trends of MOS, dye, electrolyte, sealing material and CE employed in DSSC is necessary. This paper have presented the various design strategies, material employed and literature in the field of MOS, dye, electrolyte, sealing material, and CE for DSSC. We illustrate the architecture, working mechanism, and brief explanation of DSSC growth as well as necessary requirements for the DSSC components to provide a direction for the construction of highly efficient DSSC. This paper also consolidated the introduction, benefits and classification of PV technologies. We also give brief description of market growth of DSSC technology and future perspective for efficient DSSC.